Deep Learning Principles in Nahdlatul Wathan Madrasah Curriculum (1934–1997): A Historical Perspective - Herman Zuhdi; Swastika Jonchhen (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
Purpose – This study investigates how the curriculum of Madrasah Nahdlatul Wathan (NW) from 1934 to 1997 embodied pedagogical principles aligned with modern deep learning theories. It aims to demonstrate the potential of traditional Islamic education to contribute to the design of context-based, value-oriented curricula for contemporary madrasahs. Design/methods/approach – A qualitative historical-descriptive method was employed. The research analyzed curriculum documents, teaching materials, and visual archives, alongside semi-structured interviews with NW teachers and alumni. Data were examined through content and thematic analysis, supplemented by quantitative assessment of deep learning indicators across educational levels. Findings – The findings reveal that NW’s curriculum promoted deep understanding, independent learning, social collaboration, and strong spiritual values. These principles were reflected in practices like halaqah discussions, critical text interpretation, public speaking exercises, and community engagement. Quantitative analysis showed an upward trend in deep learning principles from the elementary to the senior levels, with consistently high spiritual integration. Although developed decades ago, NW’s model parallels modern educational goals and offers insight for integrating traditional pedagogy with digital innovations such as AI-driven learning tools. Research implications/limitations – The study suggests traditional Islamic education provides rich models for developing transformative, value-based curricula. Challenges include limited archival data and reliance on retrospective interviews. Further research should explore practical frameworks for combining heritage-based pedagogies with modern technological tools.